BCT562: Bio-Composite Technology I / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2016)
The course will review the general technology of composites, and focus on the bio-based composites field, moving to a more detailed examination of the significant of bio-composites produced in Malaysia (solid materials, modified materials and laminated products like plywood, laminated veneer lumber, glued-laminated timber, and mechanically connected laminates which are based on solid, laminate and veneer based composites). It also provides an overview of wood-based composites as an increasingly important part of the wood utilization industry. The composite technology as is viable solution to material limitations in both natural and manufactured products. The development of bio-based composites maximizes the use of the forest and agricultural plantation resources. A generalized composite model is described in terms of laminates size and orientation, and adhesive systems. The product and process requirements will be considered in terms of chemical characteristics and structure; material requirements; preparation; resin technology; presses (particularly continuous press technology); panel performance requirements and test procedures; and environmental impacts of both products and processes. The performance of composite panels is considered in relation to market requirements, and from an environmental perspective. Field trips will be undertaken to familiarize students with the manufacture and recent technology of wood and bio-based composites products in Malaysia